Comparative analysis of serum galanin levels in patients with coronary artery disease with and without heart failure with reduced ejection fraction and in individuals without cardiovascular diseases - Yu. S. Timofeev; A. A. Yafarova; A. F. Sheptulina; A. R. Kiselev; V. A. Metelskaya; N. I. Dubovskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To study the level of the neuro-regulatory peptide galanin in patients with coronary artery disease (CAD) with and without heart failure with reduced ejection fraction (HFrEF) in comparison with individuals without cardiovascular disease (CVD) included in the control group.Material and methods. The study included 80 male patients as follows: 30 patients with CAD and HFrEF; 30 patients with CAD and without HFrEF; 20 individuals without CVD (control group). The groups were comparable in age and body mass index (BMI).Results. The median (Me) age of patients with CAD and HFrEF was 67,5 years, while in individuals without CVD — 56,5 years. In the CAD and HFrEF group, 73,4% of patients had New York Heart Association (NYHA) class II HF. The galanin level was significantly (p<0,001) higher in patients with CAD with HFrEF (Me [Q25-Q75] — 84,5 [62,2-96,2] pg/ml) and CHD without CHFrEF (82,9 [68,2-94,0] pg/ml compared to the control group (53,0 [24,4-62,9] pg/ml). According to the ROC analysis, the highest area under the curve (AUC=0,924) for galanin was in the CAD without HFrEF group relative to the control. At the estimated threshold level of 71,5 pg/ml, the sensitivity and specificity were 70,0% and 95,0%, respectively.Conclusion. The obtained results suggest an association between galanin and the pathophysiological mechanisms of CAD development, regardless of HFrEF.